2021
DOI: 10.1021/acs.jproteome.1c00244
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Promastigote Secretome of Seven Leishmania Species

Abstract: Leishmaniasis is one of the most impactful parasitic diseases worldwide, endangering the lives of 1 billion people every year. There are 20 different species of Leishmania able to infect humans, causing cutaneous (CL), visceral (VL), and/or mucocutaneous leishmaniasis (MCL). Leishmania parasites are known to secrete a plethora of proteins to establish infection and modulate the host's immune system. In this study, we analyzed using tandem mass spectrometry the total protein content of the secretomes produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…These proteins were also abundant in Leishmania spp. exoproteome except NADPH oxidase (Pissarra et al ., 2022). Furthermore, we compared 193 L. passim exoproteome proteins and 306 exoproteome proteins shared between seven Leishmania spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These proteins were also abundant in Leishmania spp. exoproteome except NADPH oxidase (Pissarra et al ., 2022). Furthermore, we compared 193 L. passim exoproteome proteins and 306 exoproteome proteins shared between seven Leishmania spp.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, clusterProfiler (Yu et al ., 2012) of the R software package was used to perform GO and KEGG pathway enrichment analyses. We compared 193 L. passim exoproteome proteins with 306 exoproteome proteins common between seven Leishmania spp (Pissarra et al ., 2022) using reciprocal BLASTP and 67 protein pairs showed the e-value lower than 6E-03. Among them, 55 were considered homologs with an e-value lower than 1E-50.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, in bioinformatics analysis, it was found that most of the proteins were secreted through an unconventional mechanism. The high preservation of the protein and its recognized function in the Leishmania secretome data sets further validate the recommended use of promastigote-secreted proteins as a generator for antigen discovery and the production of vaccines and drug targets [ 79 ].…”
Section: Proteomic Approach To Secreted Proteins In Leishmaniasismentioning
confidence: 87%